SOCIAL MEDIA MARKETING AS A TOOL FOR PROMOTING THE REGIONAL INVESTMENT PORTALS - A. Yu. Fadeyeva (Russian Journal of Economics and Law)
Objective: to investigate the potential of Social Media Marketing as a tool for promoting regional investment portals in the information environment, to identify the most effective ways of its implementation and to determine the level of mastering of this tool by the Russian regions. Methods: general scientific methods (observation, comparison, analysis, induction, deduction, analogy, classification). Results: the analysis showed that today Social Media Marketing is an essential tool for interaction with the investment community and one of the most effective ways to promote the regional portal, which allows to increase the knowledge of and loyalty to the brand, to increase the targeted website traffic, to increase the awareness of investors about the specific features of the portal and the regional development agencies’ functioning, to promptly receive information about the investment environment and to establish contacts with investors. At the same time, the study of SMM-activity in the Russian regions revealed a very low level of quality of communication with investors through social networks. Scientific novelty: for the first time the article investigates the significance and makes the comparative analysis of the Social Media Marketing channels with regard to investment promotion agencies, as well as the results of the regional structures functioning for effective communication through social networks. Practical significance: the main results of the research can be used by the regional investment agencies in order to promote their websites, increase the quality of communication with investors and promote the investment attractiveness of the region as a whole.